The Interpretation of Song Lyrics by Fortwnty in the Album Nalar: A Study of Riffaterre's Semiotics - Survey Sijabat; Evelin Giovani; Ekfindar Diliana (Universitas Musamus Merauke, 2023)
The purpose of this research is to know the interpretation meaning behind “Kursi Goyang”,